Consolidation therapy impact on survival outcomes in young patients with intracranial primary diffuse large B-cell lymphoma achieving complete remission: a propensity score matching analysis - Wen, Ge; Xiang, Miao; Wang, Hanyu; Wang, Jijin; Shao, Han; Zhang, Jinshan; Zhang, Yujing (Frontiers in Oncology, 2025)
ObjectivesPrimary central nervous system lymphoma is an extremely aggressive type of non-Hodgkin lymphoma, and there is no consensus regarding the optimal management strategy for this disease. This study aimed to analyze the impact of consolidation therapy among young patients with intracranial primary diffuse large B-cell lymphoma (DLBCL).MethodsThis retrospective study analyzed the clinical data of 55 young patients (age < 60 years) with intracranial primary DLBCL who achieved complete remission (CR) after high-dose methotrexate (HD-MTX)-based chemotherapy from March 2001 to October 2021. Among these patients, 33 patients received consolidation therapy, and 22 patients did not. Overall survival (OS) and disease-free survival (DFS) were compared between the two groups via Kaplan–Meier analysis, the multivariate Cox proportional hazards method, and propensity score matching (PSM).ResultsThe median follow-up time was 60.1 months. A total of 13 patients (23.6%) died, and 20 patients (36.4%) experienced recurrence. Patients who received consolidation therapy had higher 2-year OS (96.8% vs. 71.1%, P = 0.036) and DFS (90.9% vs. 56.4%, P = 0.006) rates than those without consolidation therapy. Multivariate analysis after PSM revealed that consolidation therapy was an independent predictor of DFS (HR = 0.282, 95% CI = 0.084–0.942, P = 0.040). Furthermore, rituximab was an independent predictor of favorable OS, and performance status was an independent predictor of OS and DFS. Subgroup analysis showed rituximab significantly improved OS in patients without consolidation therapy (88.9% vs. 45.0%, P = 0.006), but not in those with consolidation therapy (95.0% vs. 100%, P = 0.528).ConclusionsConsolidation therapy improved DFS in young intracranial primary DLBCL patients achieving CR after HD-MTX-based chemotherapy. Autologous stem cell transplantation and radiotherapy showed comparable consolidation benefits. Good performance status correlated with favorable outcomes. Adding rituximab to induction chemotherapy may improve OS in patients without consolidation therapy, but it might be unnecessary for those eligible for consolidation. Further research involving a larger patient cohort is warranted to ascertain rituximab’s efficacy.